The total costs of seismic retrofits: State of the art. Issue 4 (November 2021) - Fung, Juan F; Sattar, Siamak; Butry, David T; McCabe, Steven L
This article presents the current state-of-practice with respect to quantifying the total cost to retrofit an existing building. In particular, we combine quantitative, qualitative, and heuristic data to provide a taxonomy for understanding the direct and indirect costs associated with seismic risk mitigation. Much of the literature to date has focused on estimating structural retrofit costs, the costs of retrofitting the structural elements of a building. In contrast, there is very little research or data on the remaining cost components of the total cost. We propose using structural cost as the foundation for approximating the remaining cost components and the total cost itself. To validate our findings, we compare the proposed approximations with actual cost estimates developed by engineering professionals.